USING OF SATELLITE NAVIGATION IN THE PROCESS OF GEOINFORMATION COMPETENCES FORMATION OF PUPILS ON GEOGRAPHY LESSONS (Journal of Information Technologies in Education (ITE), 2017)
Satellite navigation, as one of the basic elements of geoinformation technology, becomes an integral part of the life of modern society. In this regard, we must prepare a younger generation for the necessity and expediency of practical use of satellite navigation. In addition, this direction in geoinformatics should become an integral element of the educational process, as it opens up unlimited capabilities for the teacher through the use of the navigator as an educational technical device, and global positioning technology as one of the pedagogical elements.In the article the theoretical principles of the use of satellite navigation in the formation of a geoinformation competence of pupils on geography lesson: the educational functions of the device,which it can perform in the educational process; regularities in the formation of skills in students and pedagogical obtained with the help of the navigator; the main principles of using satellite navigation in the learning process; levels of knowledge competence of schoolchildren of global positioning technologies etc.Pedagogical technologies of introducing satellite navigation into the practice of modern schools in various forms of organization of training are analyzed on concrete examples.
Keywords: satellite navigation; satellite navigator; pedagogical geoinformation; geoinformation competence; educational function of navigator